THE REAL-TIME SYSTEMS, ANALYSIS OF POSSIBILITIES OF THEIR APPLICATION IN THE MANAGEMENT OF BURLY CONSTRUCTION MACHINES - Yakovlev, S. O.; Khryshcheniuk, S. I. (Science and Transport Progress, 2008)
Presently computers are more utilized in the mode of batch processing or solution of separate jobs, which are loaded from the stand of operator. In spite of the fact that at present the advantages of the real-time systems and dialog modes of their functioning became obvious, too little attention is paid to the problem of application of these progressive methods for the management of parks of building machines.